Experimental and Theoretical Modelling of Waste Produced by the Marble Industry of Tepexi de Rodríguez - Garcia-Galicia, J. A.; Morales-Olán, G.; Cadena-Tecayehuatl, M. H.; Moreno-Zarate, P. (European Journal of Sustainable Development, 2017)
Tepexi de Rodríguez is one of the municipalities with the highest rate of extreme poverty in Mexico. The agriculture and the marble extraction industry are the major sources of employment. This region has more than 15 processing factories of marble, where poor safety conditions of work, low salaries and pollution are common denominator. The marble residues deposit in the ground without control, deteriorate the vegetation, causes desertification and affect the health of the population. Actually, there aren´t researches about the amount of waste generated by this industry in Tepexi. The objective of this work was analyze theoretically through statistical formulas the amount of waste generate in the marble transformation and compare to the real residues obtain in a field test. The results show that 87% of the raw material is discarded, generate more than 60,000 cubic meters of waste per year. With this results, can be proposed that the blocks will be standardize, optimizing the raw material by 25% or more, decreasing the amount of residues and advantage the development of industry with a sustainable approach. Keyword: Waste reduction, pollution, sustainable development, marble industry